Production of the 169Er Radionuclide Via Deuteron-Induced Reaction on 168Er: A Theoretical Study (Bangladesh Journal of Medical Physics, 2025)
This study evaluates the 168Er(d,p)169Er reaction for accelerator-based production of 169Er(t1/2 9.39d), a radionuclide widely applied in radiosynovectomy (RSV). Excitation functions were calculated up to 200 MeV using TALYS-2.0, considering six level density models, optical model, and mass model. A constant deuteron beam with the current of 5 mA irradiated a 0.025 mm thick 168Er target foil having area of 25 mm × 25 mm for 24 hours. Results showed consistent cross-section predictions across models, with an optimal excitation function between 5–20 MeV. The maximum cross-section was 128 mb at ~9 MeV, yielding a peak activity of ~540 GBq at end of bombardment (EOB), corresponding to ~4.6 GBq/mA-h. Production amounts reached 6.32 × 1017 atoms, with post-irradiation decay following expected exponential trends. These findings confirm that the 168Er(d,p)169Er route offers a reliable, high-yield, and reactor-independent pathway for localized 169Er production, enabling broader clinical access for RSV and potential therapeutic and post-RSV imaging applications.Ban. J. Med. Phys., Vol -16, Issue -1, 2025 : 24-29